Infections with the tick-borne bacterium "Candidatus Neoehrlichia mikurensis" mimic noninfectious conditions in patients with B cell malignancies or autoimmune diseases - Grankvist, Anna; Andersson, Per-Ola; Mattsson, Mattias; Sender, Monica; Vaht, Krista; Hoper, Linnea; Sakiniene, Egidija; Trysberg, Estelle; Stenson, Martin; Fehr, Jan; Pekova, Sona; Bogdan, Christian; et al. (Clinical Infectious Diseases, 2014)
Candidatus Neoehrlichia mikurensis is a newly discovered noncultivatable bacterium spread among ticks and rodents in Europe and Asia that can infect humans, particularly immunocompromised patients.We compiled clinical and laboratory data from 11 patients with hematological malignances or autoimmune diseases who were diagnosed with Candidatus N. mikurensis infection in Europe 2010-2013. Both published (6) and unpublished cases (5) were included.The patients had a median age of 67, were mostly male (8/11), and resided in Sweden, Switzerland, Germany, and the Czech Republic. All but one had ongoing or recent immune suppressive treatment and a majority were splenectomized (8/11). Less than half of them recalled tick exposure. The most frequent symptoms were fever (11/11), localized pain afflicting muscles and/or joints (8/11), vascular and thromboembolic events (6/11), that is, deep vein thrombosis (4), transitory ischemic attacks (2), pulmonary embolism (1), and arterial aneurysm (1). Typical laboratory findings were elevated C-reactive protein, leukocytosis with neutrophilia, and anemia. Median time from onset of symptoms to correct diagnosis was 2 months. In at least 4 cases, the condition was interpreted to be due to the underlying disease, and immunosuppressive therapy was scheduled. All patients recovered completely when doxycycline was administered.Candidatus N. mikurensis is an emerging tick-borne pathogen that may give rise to a systemic inflammatory syndrome in persons with hematologic or autoimmune diseases that could be mistaken for recurrence of the underlying disease and/or unrelated arteriosclerotic vascular events. Awareness of this new pathogen is warranted among rheumatologists, hematologists, oncologists, and infectious disease specialists.
EVALuna2:7651